2011
DOI: 10.1177/0884533611406133
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of DHA + EPA by Low‐Income Women During Pregnancy and Lactation

Abstract: Background: The ω‐3‐fatty acid docosahexaenoic acid (DHA) is important in infant brain development and maturation. The advisable intake of the ω‐3 fatty acids DHA and eicosapentaenoic acid (EPA) for pregnant and lactating women is 300 mg/d or 9 g/month. The objective of this cross‐sectional study was to test the hypothesis that low‐income pregnant/or lactating women do not consume advisable amounts of DHA+EPA and to determine whether any of the measured demographic factors were related to DHA and EPA consumpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
2
9
1
Order By: Relevance
“…In contrast, Nochera et al 37 found that pregnant women (2.37 g/mo) consumed more EPA+DHA when compared to lactating women (2.04 g/mo). EPA and DHA are found predominantly in cold water fish, i.e.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In contrast, Nochera et al 37 found that pregnant women (2.37 g/mo) consumed more EPA+DHA when compared to lactating women (2.04 g/mo). EPA and DHA are found predominantly in cold water fish, i.e.…”
Section: Discussionmentioning
confidence: 92%
“…Stark et al reported omega-3 fatty acid intakes for an African American population. 37 The intakes of pregnant and lactating women shown in Table 2, along with the intakes mentioned above, seem to provide evidence that pregnant and non-pregnant women are not meeting their needs for EPA and DHA intake.…”
Section: Omega-3 Fatty Acids and Infant Outcomesmentioning
confidence: 99%
See 3 more Smart Citations